New 1D chiral Zr-MOFs based on in situ imine linker formation as catalysts for asymmetric C–C coupling reactions - Nguyen, Khoa D.; Ehrling, Sebastian; Senkovska, Irena; Bon, Volodymyr; Kaskel, Stefan (Journal of Catalysis, 2020)
A novel chiral diimine Zr-MOF (DUT-136, DUT - Dresden University of Technology) is synthesized in a one-pot reaction from ZrCl4, 4-formylbenzoic acid, and (R,R)-1,2-diphenylethylenediamine as an enantiopure core. Inspired by the versatile chemistry of the C[dbnd]N bond, a variety of post-synthetic derivatizations were performed. Oxidation, reduction, and metalation effectively generated the chiral amide-, amine-, and Ni containing DUT-136 MOFs, respectively. The catalytic activity of these post-synthetically modified materials was systemically evaluated in a wide range of asymmetric organic transformations, including the Friedel-Crafts alkylation, Michael addition, aldol reaction, and the Ni-catalyzed C–C coupling.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Asymmetric C–C coupling; DUT-136; In situ imine linker formation; Metal-organic framework; Zirconium